2019
DOI: 10.1021/acs.jmedchem.9b00258
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Specific versus Nonspecific Interactions of Aggregation-Prone Inhibitors and Attenuators

Abstract: A common source of false positives in drug discovery is ligand self-association into large colloidal assemblies that nonspecifically inhibit target proteins. However, the mechanisms of aggregationbased inhibition (ABI) and ABI-attenuation by additives, such as Triton X-100 (TX) and human serum albumin (HSA), are not fully understood. Here, we investigate the molecular basis of ABI and ABI-attenuation through the lens of NMR and coupled thermodynamic cycles. We unexpectedly discover a new class of aggregating l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(70 citation statements)
references
References 102 publications
2
68
0
Order By: Relevance
“…Some Epac small-molecule inhibitors, including ESI-09, are prone to aggregation-based inhibition leading to false positives arising from nonspecific binding. The mechanisms by which additives such as Triton X-100 and serum albumin can attenuate this adverse effect have been studied in detail by combination of biophysical techniques [36]. Biochemical characterization and SAR studies indeed suggested that ESI-09 inhibited activity of both Epac1 and Epac2 at concentrations well below those that induce protein denaturation [37].…”
Section: Epac1 Competitive Inhibitorsmentioning
confidence: 99%
“…Some Epac small-molecule inhibitors, including ESI-09, are prone to aggregation-based inhibition leading to false positives arising from nonspecific binding. The mechanisms by which additives such as Triton X-100 and serum albumin can attenuate this adverse effect have been studied in detail by combination of biophysical techniques [36]. Biochemical characterization and SAR studies indeed suggested that ESI-09 inhibited activity of both Epac1 and Epac2 at concentrations well below those that induce protein denaturation [37].…”
Section: Epac1 Competitive Inhibitorsmentioning
confidence: 99%
“…This property may limit the maximum CE3F4R concentration used in therapeutic applications and increases susceptibility to non-specific effects such as aggregation-based inhibition. This led Boulton et al to investigate CE3F4R’s non-specific interactions with EPAC1 using diverse techniques with varying degrees of resolution [47]. The formation of CE3F4R aggregates in vitro was studied using two commonly-used techniques, namely dynamic light scattering (DLS) and transmission electron microscopy (TEM) [34,35,42,47].…”
Section: Specific and Non-specific Inhibition Of Epac1 By Ce3f4rmentioning
confidence: 99%
“…This led Boulton et al to investigate CE3F4R’s non-specific interactions with EPAC1 using diverse techniques with varying degrees of resolution [47]. The formation of CE3F4R aggregates in vitro was studied using two commonly-used techniques, namely dynamic light scattering (DLS) and transmission electron microscopy (TEM) [34,35,42,47]. With both techniques, sub-micrometer aggregates were observed with sizes between 60 to 900 nm [47].…”
Section: Specific and Non-specific Inhibition Of Epac1 By Ce3f4rmentioning
confidence: 99%
See 2 more Smart Citations